Assessing the key factors contributing to non-adherence to pulmonary tuberculosis treatment: a descriptive study - Mariam Lakara; Anil Kumar Patidar; Anil Sharma (Monaldi Archives for Chest Disease)
Tuberculosis (TB) remains a significant public health challenge, particularly in developing nations like India, where it imposes a considerable burden. This descriptive cross-sectional study aimed to assess the factors affecting noncompliance with TB medications among pulmonary TB patients in an Indian community. A total of 215 participants were selected through non-probability purposive sampling. Data on factors contributing to non-adherence were collected using a structured self-administered questionnaire. Demographic characteristics, including age, gender, education, marital status, occupation, habitat, income, diagnosis, and duration since diagnosis, were recorded and analyzed. Key factors contributing to non-adherence were categorized into personal, economic, social, psychological, health facility, and technological factors. The results demonstrated that the non-adherence rate was 48.3%, while 51.7% of participants exhibited adherence to TB treatment. Discontinuing medication to feel better significantly increased noncompliance risk, especially for those who stopped "most of the time" vs. those who never stopped (odds ratio = 8.693, 95% confidence interval: 3.179-23.77). This study reveals that non-adherence to pulmonary TB treatment is influenced by a range of factors, including personal, economic, social, psychological, health facility, and technological factors, highlighting the need for multifaceted interventions to improve adherence.